Wages, Employment, and STEM Education in Ohio, Pennsylvania, and West Virginia Report No. 1 (2016) - Gonzalez, Gabriella C. (RAND Corporation, 2016)
This first of five annual reports focuses on employment and wages in energy and advanced manufacturing-related industries and on science, technology, engineering, and mathematics (STEM) education indicators in the Appalachia Partnership Initiative (API) region. These reports will inform the regional stakeholder community about localities with greater demand for STEM careers and guide API investments and collaborative work.